THE EFFECT OF WORK ENVIRONMENT AND ORGANIZATIONAL COMMITMENT TOWARDS EMPLOYEES’ TURNOVER INTENTION IN YAYASAN MEDIKA GMIM - Sofryan Injillion Pelealu; David P.E Saerang; Shinta J.C Wangke (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2022)
Human resources or employees are necessary for every company or organization, whether the company is large or small, because every company needs human resources to carry out various activities related to the continuity of the company. Every company or organization regardless of its location, size or nature of the business has always given a key concern about employees’ turnover intention, if the turnover occurs in a company, then the company will lose some of its employees and should replace them with the new ones. The objective of this research is to analyze the effect of work environment and organizational commitment on employees’ turnover intention in Yayasan Medika GMIM. This research was conducted through quantitative approach and the multiple regression analysis was used to analyze the effect of the independent variables on the dependent variable. This research was also conducted using 100 employees of Yayasan Medika as the respondents for the questionnaire. The result of this research found that work environment and organizational commitment have significant and negative effect on employees’ turnover intention simultaneously and separately.